Are guideline-recommended risk classification schemes in pulmonary hypertension adequately robust to guide the real-world setting - KOCAKAYA, DERYA (My University, 2023)
Background: Pulmonary hypertension is a complex syndrome that encompasses a diverse group of pathophysiologies predisposed by different environmental and genetic factors. It is not clear to which extent the universal risk classification schemes can be applied to cohorts in individual pulmonary hypertension centers with differing environmental backgrounds, genetic pools, referral networks. Aims: We sought to explore whether the recommended risk classification schemes could reliably be used for mortality prediction in an unselected pulmonary hypertension population of a tertiary pulmonary hypertension center. Study Design: A retrospective cross-sectional study. Methods: We retrospectively screened our hospital database for the patients with pulmonary hypertension between 2015 and 2022. We compared the predicted and observed mortality rates of several risk classifications schemes. Results: We identified 723 cases in our PH database, the final study population consisted of 549 patients. The REVEAL, REVEAL-Lite and European Society of Cardiology/European Respiratory Society risk scores significantly underestimated the mortality risk in the lowrisk stratum (5.3% vs. 1.9%, P < 0.001; 5.3% vs. 2.9%, P = 0.015 and 6.3% vs. 1%, P < 0.001, respectively) and overestimated the mortality risk in the high-risk stratum (11.8% vs. 25.8%, P < 0.001; 10.4% vs. 25.1%, P < 0.001 and 13.2% vs. 30%, P < 0.001, respectively). Although the COMPERA 4-strata model significantly underestimated the risk in low- and intermediate-low risk strata (4.9% vs. 1.5%, P < 0.001 and 6.8% vs. 2.8%, P = 0.001, respectively), it was accurate in intermediate-high and high-risk groups (10.1% vs. 8.7%, P = 0.592 and 15.6% vs. 22%, P = 0.384, respectively). The analyses limited only to group 1 pulmonary hypertension patients gave similar results. Conclusion: The established risk classification schemes may not perform as good as expected in unselected PH populations and this may have important implications on management decisions. Tertiary centers should not uncritically accept the published risk prediction models and consider modifying current risk scores according to their own patient characteristics.